Fire safety management in Historical Government building / Nurul Fatihah Che Wil - Che Wil, Nurul Fatihah (Faculty of Architecture, Planning and Surveying, 2015)
Fire is the biggest threat to the occupants, contents, buildings and others. Normally, fire that occurred can cause loss of life and also property. Other than that, fire is the human enemies because the nature of fire which can bring death and environmental destruction such as haze, air pollution, illness and others. Fire safety represents a major aspect of the design, construction and operation of historical government building. Meanwhile, the fire safety management is one of the important aspects in a building. It also can reduce the risk of damage to the contents, property and building. Besides that, it also can reduce injuries to occupants in the event of the fire or other emergency. The problem statement in this study is the conflict between fire safety management with conservation of historical government building, lack of fire safety management and the following fire safety requirements in law. The issues of heritage buildings in Malaysia not have comprehensive fire safety regulations and guidelines. The aims and objectives of these studies are; the first to identify the fire safety management at historical government buildings. Secondly, to identify the problem in the management of fire safety and the third, recommend the approach that should be taken in improving management of fire safety. The research methodology involved in this study is; the first stage identify the latest issues and problems. It is the process for the aims and objectives of the study is achieved. The second stage is identify of objectives in this study, the objectives of study will be achieved through the research conducted accordingly. The third stage is collecting data and information, the sources are divided into two categories which are the primary and secondary source. The primary data involved questionnaire survey and semi - structured interview session. Other than that, the secondary data such as academic article, books, journal, paper cutting, magazines and website. The fourth stage is finding and analysis the data and the last stage is a conclusion and recommendation.